Infection and autoimmunity - Shoenfeld, Yehuda, 1948-; Rose, Noel R. (Elsevier, 2004)
Autoimmune diseases are conditions where the immune system attacks the body organs instead of foreign invaders. This book deals with the various mechanisms which infectious agents can trigger autoimmunity such as molecular mimicry, polyclonal activation and others. An overview is given with regard to bacteria, viruses and parasites associated with autoimmunity. There is a summary on classical autoimmune diseases and the infecting agents that can induce them.